The interplay between autophagy and cGAS-STING signaling and its implications for cancer - Schmid, Maximilian; Fischer, Patrick; Engl, Magdalena; Widder, Joachim; Kerschbaum-Gruber, Sylvia; Slade, Dea (Frontiers in Immunology, 2024)
Autophagy is an intracellular process that targets various cargos for degradation, including members of the cGAS-STING signaling cascade. cGAS-STING senses cytosolic double-stranded DNA and triggers an innate immune response through type I interferons. Emerging evidence suggests that autophagy plays a crucial role in regulating and fine-tuning cGAS-STING signaling. Reciprocally, cGAS-STING pathway members can actively induce canonical as well as various non-canonical forms of autophagy, establishing a regulatory network of feedback mechanisms that alter both the cGAS-STING and the autophagic pathway. The crosstalk between autophagy and the cGAS-STING pathway impacts a wide variety of cellular processes such as protection against pathogenic infections as well as signaling in neurodegenerative disease, autoinflammatory disease and cancer. Here we provide a comprehensive overview of the mechanisms involved in autophagy and cGAS-STING signaling, with a specific focus on the interactions between the two pathways and their importance for cancer.